U.S. Young Adult Numeracy Skills Lagging Behind: Results from the Newest PIAAC Release 2012/2014 - Derek E Holliday; Emily Pawlowski (Adult Education Research Conference, 2017)
This paper analyzes the numeracy skills of U.S. young adults in comparison with selected peer countries using data from the Program for the International Assessment of Adult Competencies (PIAAC).
Keywords: PIAAC; Young Adults; Numeracy